2013
DOI: 10.1063/1.4772783
|View full text |Cite
|
Sign up to set email alerts
|

Large thermal conductivity decrease in point defective Bi2Te3 bulk materials and superlattices

Abstract: Defective Bi2Te3 structures have been studied with the aim of lowering the thermal conductivity in order to improve the thermoelectric figure of merit. The cross-plane thermal conductivities of structures containing point defects have been computed by means of molecular dynamics techniques, finding a maximum decrease of 70% for a 4% concentration of tellurium atom vacancies. Superlattices with modified stoichiometries have also been considered in order to find the configuration having the lowest thermal conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 46 publications
2
50
1
Order By: Relevance
“…3,38,40 Defects V 000 Bi (or V 000 Sb ) and V Te are effective scatters of short-wavelength (high-frequency) phonons because of the larger mass and size differences between the occupied sites and the vacancies. 32,44 Therefore, these multiscale microstructures effectively reduce the κ L over a wide temperature range. As a result, a maximum zT of~1.4 at 500 K and an average zT av~1 .3 between 400 and 600 K are achieved in Bi 0.3 Sb 1.625 In 0.075 Te 3 upon In doping and HD in this work (Figure 1d), demonstrating the promise of these materials for mid-temperature power generation.…”
Section: Introductionmentioning
confidence: 99%
“…3,38,40 Defects V 000 Bi (or V 000 Sb ) and V Te are effective scatters of short-wavelength (high-frequency) phonons because of the larger mass and size differences between the occupied sites and the vacancies. 32,44 Therefore, these multiscale microstructures effectively reduce the κ L over a wide temperature range. As a result, a maximum zT of~1.4 at 500 K and an average zT av~1 .3 between 400 and 600 K are achieved in Bi 0.3 Sb 1.625 In 0.075 Te 3 upon In doping and HD in this work (Figure 1d), demonstrating the promise of these materials for mid-temperature power generation.…”
Section: Introductionmentioning
confidence: 99%
“…Many scientific attempts have been made to improve their TE performance by controlling the thermal conductivity [6][7][8][9][10][11][12][13]. At the atomic scale, it is shown that the κ l can be greatly reduced by introducing point defects, which help to scatter phonons [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been carried out to improve the thermoelectric properties by tuning the carrier concentration [15], engineering the band structure [16], or reducing the lattice thermal conductivity [17]. Halogen atoms such as I and Br act as electron donors while group-IV (Ge, Sn, Pb), group-V (As, Sb, Bi) and transition elements (Cu, Ag, Au) act as acceptors [18].…”
Section: Introductionmentioning
confidence: 99%